Direct measurement of light and heavy antibody chains using ion mobility and middle-down mass spectrometry. Issue 8 (17th November 2019) - Melani, Rafael D.; Srzentić, Kristina; Gerbasi, Vincent R.; McGee, John P.; Huguet, Romain; Fornelli, Luca; Kelleher, Neil L.
ABSTRACT: The analysis of monoclonal antibodies (mAbs) by a middle-down mass spectrometry (MS) approach is a growing field that attracts the attention of many researchers and biopharmaceutical companies. Usually, liquid fractionation techniques are used to separate mAbs polypeptides chains before MS analysis. Gas-phase fractionation techniques such as high-field asymmetric waveform ion mobility spectrometry (FAIMS) can replace liquid-based separations and reduce both analysis time and cost. Here, we present a rapid FAIMS tandem MS method capable of characterizing the polypeptide sequence of mAbs light and heavy chains in an unprecedented, easy, and fast fashion. This new method uses commercially available instruments and takes 24 min, which is 40-60% faster than regular liquid chromatography-MS/MS analysis, to acquire fragmentation data using different dissociation methods.